دور التمويل الذاتي في إعادة اعمار الوحدات الحكومية غير الهادفة للربح "دراسة تطبيقية في كلية الإدارة والاقتصاد/ جامعة بغداد" - ياسين سناء احمد (Journal of Economics and Administrative Sciences, 2010)
The Iraqi non profit governmental units are facing great financing challenges in providing the money required for reconstructing the damages occurred after 9th of April 2003. Related to that, This research, which is contained of studying the self – financing experiment in non profit governmental units which is considered one of the financing alternatives that contribute in providing the required money to meet the shortage of central finance; and creating the economic exploitation for the resources and possibilities achieved by the non profit governmental units themselves for the purpose of employ them in reconstruction and to reduce the burden on the public budget which is responsible of financing the activities of these units through the central financing.